ENTREPRENEURSHIP EDUCATION OF A HOLISTICALLY COMPREHENDED PERSONALITY AS AN ASSUMPTION INFLUENCING LIFE QUALITY - Bieliauskiene, Rita; Visockaite, Asta (European Scientific Journal, ESJ, 2014)
Purpose - The article presents an original authors‘view to the comprehension of a holistically comprehended essence of an entire personality. In addition, article reviews wide scientific literature, EU and Lithuanian governmental documents, programs accepted in the educational community, problematic of youth entrepreneurship education. The goal of the article is to define the entrepreneurship education of such personality which would be an essential assumption, having influence for better life quality. Design/methodology/approach - analyses of the scientific literature. Findings and originality – The scientific problem formed is based on an interdisciplinary thinking (philosophy, management, education, psychology). Scientific novelty emerges in the presented value-concenptions of a personality, coherence of person‘s entrepreneurship and life quality. Research type: literature review. This research is funded by the European Social Fund under the Global Grant measure (No. VP1-3.1-ŠMM-07-K-03-032)